2003
DOI: 10.1097/01.jcp.0000095348.32154.ec
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomized, Placebo-Controlled Trial of Olanzapine in the Prevention of Psychotic Relapse

Abstract: Sustained response to antipsychotic therapy is an important outcome measure for patients with psychotic disorders. Placebo control in studies of relapse prevention contributes valuable information yet provokes much debate. This study, using placebo as a control, evaluated olanzapine's efficacy in preventing a psychotic relapse. Participants were stable minimally symptomatic outpatients with schizophrenia or schizoaffective disorder. The study included 4 phases: (1) 4-day to 9-day screening/evaluation (N = 583)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 34 publications
1
39
1
4
Order By: Relevance
“…Since the last PORT review, 5 studies have examined the comparative efficacy of an SGA and placebo for the prevention of relapse in schizophrenia. [40][41][42][43][44] These studies have documented the superior efficacy of aripiprazole, olanzapine, paliperidone, quetiapine, and ziprasidone compared with placebo for preventing relapse.…”
Section: Maintenance Antipsychotic Medication Treatmentmentioning
confidence: 99%
“…Since the last PORT review, 5 studies have examined the comparative efficacy of an SGA and placebo for the prevention of relapse in schizophrenia. [40][41][42][43][44] These studies have documented the superior efficacy of aripiprazole, olanzapine, paliperidone, quetiapine, and ziprasidone compared with placebo for preventing relapse.…”
Section: Maintenance Antipsychotic Medication Treatmentmentioning
confidence: 99%
“…Quality of life Two olanzapine studies 20,41 found olanzapine significantly superior to placebo on overall quality of life (N = 2, n = 406, SMD = À0.38, CI: À0.59 to À0.17, P = 0.0003). Mö ller et al 23 found no significant superiority of zotepine (combined effect on the physical and the psychic components of the SF-36 scale: n = 72, SMD = À0.24, CI: À0.70 to 0.22, P = 0.309).…”
Section: Molecular Psychiatrymentioning
confidence: 99%
“…Data about changes in glucose concentrations have been presented from 5,607 patients with schizophrenia or schizophreniform illness recruited in 12 prospective randomised clinical trials, of which 11 were double-blind [1,[39][40][41][42][43][44][45][46][47][48][49] (Table 2). Of these studies, eight lasted for at least 6 months and four lasted for more than 1 year.…”
Section: Consistency Of Associationmentioning
confidence: 99%